Chemical composition and acaricidal activity of essential oils from Alpinia zerumbet, Bixa orellana, Mesosphaerum suaveolens and Syzygium cumini against Oligonychus punicae on clonal seedlings of Eucalyptus grandis - Adriele de Castro Ferreira; Rosenya Michely Cintra Filgueiras; Paulo Roberto Ramalho Silva; Izaias Santos Marques; Antonio José Cantanhede Filho; Bruno de Araújo Gomes; Edson Rodrigues Filho; Franciele Costa de Sousa; Eslane Reis Farias Mendes; Helane Cristina De Andrade Rodrigues Severo; Alyne Freire de Melo; Kamilla de Andrade Dutra; et al. (Crop Protection, 2026)

Combining wood traits as a promising timber origin verification and its application in the Brazilian trade chain - Bruna Hornink; Daigard Ricardo Ortega-Rodriguez; Deoclecio J. Amorim; Peter Groenendijk; Kathelyn Paredes-Villanueva; José Guilherme Roquette; Ana Carolina M.C. Barbosa; Edson Vidal; Alexandre Bahia Gontijo; Monique S. Costa; Norma Rodrigues Nunes de Senna; Davi Neves de Lemos; et al. (Science of The Total Environment, 2025)

Three-dimensional discrete magnetic inversion using graph theory to determine the framework of isolated sources - Rômulo Rodrigues de Oliveira; Rodrigo Bijani; Nelson Ribeiro-Filho; Edson Alonso Falla-Luza; Cosme F. Ponte-Neto (Journal of Applied Geophysics, 2025)

Essential oils of Alpinia zerumbet, Syzygium cumini, and Aniba rosaeodora: toxicity, effects on nutritional components, and biological parameters of Spodoptera frugiperda (Lepidoptera: Noctuidae) - Daniele Muniz dos Reis; Solange Maria de França; Izaias Santos Marques; Glaucilane dos Santos Cruz; Antonio José Cantanhede Filho; Bruno de Araújo Gomes; Edson Rodrigues Filho; Alan Mario Zuffo; Douglas Rafael eSilva Barbosa (Journal of Plant Diseases and Protection, 2025)

Leveraging Antarctic psychrotolerant fungi for PAH biodegradation, unveiling key factors influencing the process - Alef dos Santos; Willian Garcia Birolli; Felipe Oliveira Souza; Patrícia Giovanella; Lucélia Cabral; Gabriele Santana de Farias; Eduardo Jorge Pilau; Lara Durães Sette; Edson Rodrigues-Filho (Chemosphere, 2025)

Bacteria isolated from Aedes aegypti with potential vector control applications - Juan Campos de Oliveira; Ricardo de Melo Katak; Veranilce Alves Muniz; Marta Rodrigues de Oliveira; Elerson Matos Rocha; William Ribeiro da Silva; Edson Júnior do Carmo; Rosemary Aparecida Roque; Osvaldo Marinotti; Olle Terenius; Spartaco Astolfi-Filho (Journal of Invertebrate Pathology, 2024)

Polyurethane sponges bearing cucurbituril adsorb Cr(III) and Pb(II) ions from contaminated water samples - Lilian Rodrigues Rosa Souza; Renato Salviato Cicolani; Bruno Edson Santana de Freitas; Giovana Lavezo Floriano; Maycon Lucas de Oliveira; Antonio Gustavo Sampaio de Oliveira Filho; Márcia Andreia Mesquita Silva da Veiga; Gregoire Jean-François Demets (Environmental Science and Pollution Research, 2024)

Does non-steroidal anti-inflammatory drugs-related preemptive analgesia modulate SOCS3/IL-6 pathway in oral surgery? - Assis Filipe Medeiros Albuquerque; José Jackson do Nascimento Costa; José Roberto Viana Silva; Paulo Goberlânio de Barros Silva; Filipe Nobre Chaves; Eduardo Frederico Eduardo Maferano; Edson Luiz Cetira Filho; Karuza Maria Alves Pereira; Sérgio Lima Santiago; Thyciana Rodrigues Ribeiro; Fábio Wildson Gurgel Costa (Inflammopharmacology, 2024)

Deep4Fusion: A Deep FORage Fusion framework for high-throughput phenotyping for green and dry matter yield traits - Lucas de Souza Rodrigues; Edmar Caixeta Filho; Kenzo Sakiyama; Mateus Figueiredo Santos; Liana Jank; Camilo Carromeu; Eloise Silveira; Edson Takashi Matsubara; José Marcato; Wesley Nunes Goncalves (Computers and Electronics in Agriculture, 2023)

Endophytic, extremophilic and entomophilic fungi strains biodegrade anthracene showing potential for bioremediation - Erika Bonatti; Alef dos Santos; Willian Garcia Birolli; Edson Rodrigues-Filho (World Journal of Microbiology and Biotechnology, 2023)

Synthetic dibenzylideneketones as promising anti-herpes simplex virus type 1 agents - Thalita Zago Oliveira; Dyenefer Pereira Fonseca; André Henrique dos Santos; Thays Rosa da Silva; Danielle Lazarin-Bidóia; Zia Ud Din; Benedito Prado Dias Filho; Celso Vataru Nakamura; Edson Rodrigues-Filho; Tania Ueda-Nakamura (Archives of Virology, 2023)

NEOTROPICAL FRESHWATER FISHES : A dataset of occurrence and abundance of freshwater fishes in the Neotropics - Lívia Helena Tonella; Renata Ruaro; Vanessa Salete Daga; Diego Azevedo Zoccal Garcia; Oscar Barroso Vitorino; Tatiana Lobato‐de Magalhães; Roberto Esser dos Reis; Fabio Di Dario; Ana Cristina Petry; Michael Maia Mincarone; Luciano Fogaça de Assis Montag; Paulo Santos Pompeu; et al. (Ecology, 2023)
The Neotropical region hosts 4225 freshwater fish species, ranking first among the world's most diverse regions for freshwater fishes. Our NEOTROPICAL FRESHWATER FISHES data set is the first to produce a large‐scale Neotropical freshwater fish inventory, covering the entire Neotropical region from Mexico and the Caribbean in the north to the southern limits in Argentina, Paraguay, Chile, and Uruguay. We compiled 185,787 distribution records, with unique georeferenced coordinates, for the 4225 species, represented by occurrence and abundance data. The number of species for the most numerous orders are as follows: Characiformes (1289), Siluriformes (1384), Cichliformes (354), Cyprinodontiformes (245), and Gymnotiformes (135). The most recorded species was the characid Astyanax fasciatus (4696 records). We registered 116,802 distribution records for native species, compared to 1802 distribution records for nonnative species. The main aim of the NEOTROPICAL FRESHWATER FISHES data set was to make these occurrence and abundance data accessible for international researchers to develop ecological and macroecological studies, from local to regional scales, with focal fish species, families, or orders. We anticipate that the NEOTROPICAL FRESHWATER FISHES data set will be valuable for studies on a wide range of ecological processes, such as trophic cascades, fishery pressure, the effects of habitat loss and fragmentation, and the impacts of species invasion and climate change. There are no copyright restrictions on the data, and please cite this data paper when using the data in publications.

New Δ 8,9 -pregnene steroids isolated from the extremophile fungus Exophiala oligosperma - Alef dos Santos; Edson Rodrigues-Filho (Natural Product Research, 2021)

Nitrogen use efficiency and recovery in a wheat-corn rotation under tropical savannah conditions - Fernando Shintate Galindo; Edson Cabral da Silva; Paulo Humberto Pagliari; Guilherme Carlos Fernandes; Willian Lima Rodrigues; Antônio Leonardo Campos Biagini; Eduardo Bianchi Baratella; Castro Alves da Silva Júnior; Mário João Moretti Neto; Takashi Muraoka; Marcelo Carvalho Minhoto Teixeira Filho (Nutrient Cycling in Agroecosystems, 2021)

MALDI-TOF mass spectrometry–based identification of Eurotiales from different substrates and locations in Brazil - Emanuelle B. Cardoso; Douglas Ferreira; Gláucia M. Moreira; Ludwig H. Pfenning; Edson Rodrigues-Filho; Lucas M. Abreu (Mycological Progress, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Industrial Quality of Sugarcane Under Fertigation with Nitrogen and Zinc - Fernando Nobre Cunha; Marconi Batista Teixeira; Frederico Antonio Loureiro Soares; Edson Cabral da Silva; Antonio Evami Cavalcante Sousa; Leonardo Nazário Silva dos Santos; Nelmício Furtado da Silva; Wilker Alves Morais; Vitor Marques Vidal; Fernando Rodrigues Cabral Filho; Gustavo da Silva Vieira (Sugar Tech, 2020)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

How are local fish communities structured in Brazilian semiarid headwater streams? - Carlos Alberto de Sousa Rodrigues-Filho; Ronaldo César Gurgel-Lourenço; Luis Artur Valões Bezerra; Edson Fontes de Oliveira; Rafael Pereira Leitão; Danielle Sequeira Garcez; Jorge Iván Sánchez-Botero (Hydrobiologia, 2018)

What governs the functional diversity patterns of fishes in the headwater streams of the humid forest enclaves: environmental conditions, taxonomic diversity or biotic interactions? - Carlos Alberto Sousa Rodrigues-Filho; Ronaldo César Gurgel-Lourenço; Sergio Maia Queiroz Lima; Edson Fontes de Oliveira; Jorge Iván Sánchez-Botero (Environmental Biology of Fishes, 2017)

A3K2A3-induced apoptotic cell death of Leishmania amazonensis occurs through caspase- and ATP-dependent mitochondrial dysfunction - Francielle Pelegrin Garcia; Jean Henrique da Silva Rodrigues; Zia Ud Din; Edson Rodrigues-Filho; Tânia Ueda-Nakamura; Rachel Auzély-Velty; Celso Vataru Nakamura (Apoptosis, 2017)

Cytotoxic compounds from the marine-derived fungus Aspergillus sp. recovered from the sediments of the Brazilian coast - Natália N. Saraiva; Bárbara S.F. Rodrigues; Paula C. Jimenez; Larissa A. Guimarães; Maria C.M. Torres; Edson Rodrigues-Filho; Ludwig H. Pfenning; Lucas M. Abreu; Jair Mafezoli; Marcos C. de Mattos; Letícia V. Costa-Lotufo; Maria da Conceição F. de Oliveira (Natural Product Research, 2015)

Mauritic acid: a new dammarane triterpene from the roots of Mauritia flexuosa L.f. (Arecaceae) - Hector H.F. Koolen; Elzalina R. Soares; Felipe M.A. da Silva; Aimêe A. de Oliveira; Antonia Q.L. de Souza; Lívia S. de Medeiros; Edson Rodrigues-Filho; Bruno C. Cavalcanti; Cláudia O. Pessoa; Manoel O. Moraes; Marcos J. Salvador; Afonso D.L. de Souza (Natural Product Research, 2013)

An antimicrobial diketopiperazine alkaloid and co-metabolites from an endophytic strain of Gliocladium isolated from Strychnos cf. toxifera - Hector Henrique Ferreira Koolen; Elzalina Ribeiro Soares; Felipe Moura Araújo da Silva; Antonia Queiroz Lima de Souza; Lívia Soman de Medeiros; Edson Rodrigues Filho; Richardson Alves de Almeida; Ismael Alexandre Ribeiro; Cláudia do Ó Pessoa; Manoel Odorico de Morais; Patrícia Marçal da Costa; Afonso Duarte Leão de Souza (Natural Product Research, 2012)

Electrophysiological Responses of Female and Male Hypsipyla grandella (Zeller) to Swietenia macrophylla Essential Oils - Marisi G. Soares; Luciane G. Batista-Pereira; João B. Fernandes; Arlene G. Corrêa; M. Fátima G. F. Da Silva; Paulo C. Vieira; Edson Rodrigues Filho; Orlando S. Ohashi (Journal of Chemical Ecology, 2003)